2003
DOI: 10.5614/itbj.eng.sci.2003.35.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Surface Wave Attenuation in Mangrove Forests

Abstract: Abstract. This paper presents an analytical study on surface wave attenuation in mangrove forest using analytical model developed by Massel et.al. (1999). The energy dissipation in the frequency domain is determined by treating the mangrove forest as a random media with certain characteristics using the geometry of mangrove trunks and their locations. Initial nonlinear governing equations are linearized using the concept of minimalization in the stochastic sense and interactions between mangrove trunks and roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…For the high density forest, the wave height reduction rate was higher. Hadi et al (2003) in their numerical studies also found that the rate of wave energy dissipation was higher for the case of denser mangrove forests.…”
Section: Factors Influencing Performance Of Mangrovementioning
confidence: 85%
See 1 more Smart Citation
“…For the high density forest, the wave height reduction rate was higher. Hadi et al (2003) in their numerical studies also found that the rate of wave energy dissipation was higher for the case of denser mangrove forests.…”
Section: Factors Influencing Performance Of Mangrovementioning
confidence: 85%
“…On the other hand, Hiraishi and Harada (2003) simulated the tsunami reduction effect of coastal trees with higher density of 0.3 trees/m² and reported that it would require a reduced forest width of 100 m to give wave height reduction of more than 50%. Hadi et al (2003) analyzed two types of mangrove forests, namely Rhizophora and Ceriops forests and found that Rhizophora forest attenuated wave energy most effectively. They also suggested that the resulting rate of wave energy attenuation depended strongly on the density of mangrove forest and on the diameter of mangrove roots and trunks.…”
Section: Previous Researchesmentioning
confidence: 99%
“…The drag friction slows down the wave motion's propagation into the mangrove forests [24,25,26]. The waves subsequently lose part of their energy and, therefore, attenuating them.…”
Section: Figure 2 Wave Attenuation By Mangrovesmentioning
confidence: 99%
“…[20] studied sediment transport brought by tidal currents in mangrove forest. Mangrove forest reduces the forward speed of waves, resulting in a smaller flooded area [21]. [22] observed steady channel flow with uniform inlet flow velocity 0.2 m/s and flow in creeks with wave amplitude 1 m to study the blockage characteristics and the drag force of Mangroves.…”
Section: Introductionmentioning
confidence: 99%